Enhancing Quality Software Through CMMI-ISO 9001:2008and ISO 9126 - Agus Sukoco (International Conference on Engineering and Technology Development (ICETD), 2013)
One of the software development standards in use today is the Capability Maturity Model Integration (CMMI) of the Software Engineering Institute (SEI) and ISO 9126 .Based on the 2009 survey conducted by PornchaiMongkolnam, in Asia there has been a 1,901 CMMI appraisal, to the North American continent as 1328, as many as 536 Europe, and South America 289 CMMI assessment. In India alone there has been a 409 CMMI appraisal, including three world ranking, making India the more trusted by the world International for application development. Meanwhile in Indonesia CMMI implementation is not too meaningful. Only a mixture of two companies (foreign and local) that implements it. That was probably due to the application of the mandatory in the meet (mandatory) from its headquarters abroad or indeed the company began to enter into foreign markets that require CMMI certification. This study seeks to help measure the maturity of software development using an integrated approach between CMMI and ISO 9126 in a local development company. Hopefully this can be more give their views so as to facilitate its peers able to take to implement the same thing.ISO 9001 is a standard for quality management systems while CMMI is a model for process improvement. If an organization that has achievedISO registration wishes to improve  processescontinuously, CMMI can be a strong candidatebecause it provides a more detailed roadmap forprocess improvement. However, with respect toadopting CMMI in organizations that are familiarwith ISO 9001, there are some issues that need to beresolved. For example, ISO 9001 and CMMI havedifferent targets, intent, and quantity of detail. In thispaper, we present an integrated model of ISO9001:2000 and CMMI and ISO 9126, which would resolve the aboveproblems. We expect that this model will be a usefultool for ISO registered organizations aim to attainhigher CMMI levels.